2018
DOI: 10.3126/jbpkihs.v1i1.19751
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of hematological malignancies diagnosed by peripheral smear examination

Abstract: Background: Leukemia is a malignant neoplasm of the hematopoietic stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…A study conducted in a tertiary level hospital in Eastern Region of Nepal found the M: F ratio as 1.8:1.2 Similarly, another study in the same region calculated the patients as 54% males and 46% females. 7 Similar findings were observed in other studies. 8,9 Our study included age group from 2 to 99 years.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A study conducted in a tertiary level hospital in Eastern Region of Nepal found the M: F ratio as 1.8:1.2 Similarly, another study in the same region calculated the patients as 54% males and 46% females. 7 Similar findings were observed in other studies. 8,9 Our study included age group from 2 to 99 years.…”
Section: Discussionsupporting
confidence: 88%
“…38.26% 2 and 26.91 percent. 7 Lymphoma: In our study the incidence of lymphoma was 49.3%. It is much higher than reported in India in a study i.e.…”
Section: Chronic Leukemiasupporting
confidence: 44%